Morbidity and Mortality Conference for Percutaneous Coronary Intervention. Issue 8 (August 2017) - Doll, Jacob A.; Overton, Robert; Patel, Manesh R.; Rao, Sunil V.; Sketch, Michael H.; Harrison, J. Kevin; Tcheng, James E.
Abstract : Background—: Morbidity and mortality conference is a common educational and quality improvement activity performed in cardiac catheterization laboratories, but best practices for case selection and for maximizing the effectiveness of peer review have not been determined. Methods and Results—: We reviewed the 10-year percutaneous coronary intervention morbidity and mortality conference experience of an academic medical center. Cases were triggered for review by the occurrence of prespecified procedural events. Summary reports from morbidity and mortality conference discussions were linked to clinical data from the Duke Databank for Cardiovascular Disease to compare baseline and procedural characteristics and to assess postdischarge outcomes. Of 11 786 procedures, from 2004 to 2013, 157 (1.3%) were triggered for review. The most frequent triggering events were cardioversion/defibrillation (72, 0.6%), unplanned use of mechanical circulatory support (64, 0.5%), and major dissection (41, 0.3%). Selected procedures were more likely to include high-risk features, such as ST-segment–elevation myocardial infarction, cardiogenic shock, and multivessel disease, and were associated with higher mortality at 30 days. Only a minority of triggering events were caused by controversial or unacceptable physician behavior. Conclusions—: This 10-year experience outlines the processes for conduct of an effective percutaneous coronary intervention morbidity and mortality conference, including a novel approach to case selection and structured peer review leading to actionable quality interventions. The prespecified clinical triggers, captured in the natural workflow by laboratory staff, identified complex cases that were associated with poor patient outcomes.